FORMATIVE ASSESSMENT VS SUMMATIVE ASSESSMENT: A CASE STUDY OF ESP LECTURERS IN UNIVERSITY IN INDONESIA AND THAILAND - Dwita Laksmita Rachmawati; Yufenti Oktafiah; Dwi Budiarti (Universitas Muhammadiyah Makassar, 2023)
Providing an assessment and feedbacks are crucial parts for teaching and learning phase as well as for continued growth in the education system. In general, assessing the students’ progress and giving feedbacks as reflections of progress can be done in a variety of ways. The recent research is primarily concerned with how the formative assessment, as the most advantageous and beneficial kind of evaluation can be considered as a sufficient contributor to the instruction process, particularly once followed by genuine constructive feedbacks. This research's findings claimed that the formative assessment and feedbacks have a significant impact on what the learners perform and how the instructors teach. This research explored how formative assessment is implemented in ESP classes, particularly in Business English classes at universities in Indonesia and Thailand.